The mental health of Ukrainian refugees: a narrative review - Emily Ellis; Cassie Hazell; Oliver Mason (Academia Medicine)
There are currently over 6.5 million Ukrainian refugees worldwide and this number is growing. Previous research has highlighted refugees’ vulnerability and increased risk of developing mental health problems, and there has been a growing body of research focusing on Ukrainian refugees specifically since the Russo-Ukrainian war began in February 2022. The aim of this review is to explore the current literature on the mental health of Ukrainian refugees. A systematic search was carried out and identified 21 relevant papers that met inclusion criteria. Common themes were generated using narrative synthesis principles across the included papers. Four themes were identified: (1) General Psychological Distress, (2) Common Mental Health Problems, (3) PTSD and Trauma, and (4) Coping and Resilience. This review sheds light on the current mental health of Ukrainian refugees and highlights a number of risk and mitigating factors in relation to specific mental health conditions. Implications for future research, interventions, and support are discussed, and the strengths and limitations are considered.